Permasalahan Hukum Dalam Perjanjian Sewa Beli Kapal Tanker Dengan Tanpa Awak Kapal (Bare Boat Hire Purchase) - Noviriska (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
The lease and purchase agreement is a practice that has been recognized as valid according to jurisprudence. in the UK the lease is regulated by the Hire Purchase Act 1965 and the form of the agreement adopts an open system. The background of the lease-purchase in the issue of tanker ownership or bare boat hire purchase is intended to have a vessel with a payment system for vessel purchases in installments, so that the costs incurred are not too heavy when compared to buying tankers with a cash payment system. The lease purchase agreement is a creation of practice (custom) that has been legally recognized according to jurisprudence. According to the Decree of the Minister of Trade and Industry No. 34/KP/II/80 concerning Licensing of Lease and Purchase Business Activities, buying and selling with installments and rent is regulated in Article 1 paragraph 2. In this tanker ship charter, the provisions for loss insurance have been stipulated for compensate for any losses that may arise. But how does this happen if the ship sinks while the installments that have been paid part of the payment have come in, is there any compensation? but between theory and practice are incompatible because there are considerations about this.